Current Knowledge on the Transportation by Road of Cattle, including Unweaned Calves - Kelly Buckham-Sporer; Bernadette Earley; Sonia Marti (Animals, 2023)
Transport conditions have the potential to alter the physiological responses of animals to the psychological or physical stress of transport. Transportation may introduce multiple physical and psychological stressors to unweaned calves and adult cattle, including noise, overcrowding, food and water deprivation, extreme temperatures, commingling with unfamiliar animals, handling by unfamiliar humans, and being placed in a novel environment upon arrival. Apart from these factors, the type of road and even driving skill may affect the welfare of animals. One of the concerns regarding cattle transport is that the handling and marketing of animals prior to a journey may lengthen the period of feed withdrawal. Furthermore, feed withdrawal can impact animal welfare through hunger and metabolic stress. Transportation is also associated with a decrease in animal performance as well as an increase in the incidence of bovine respiratory disease. It is well established that the transportation of cattle is a stressor that causes a quantifiable response; however, excessive stress during transport resulting in physiological or pathological changes can be reduced with best management practices. The objective of this review was to analyse the available scientific literature pertaining to the transport by road of cattle, including unweaned calves.